2008
DOI: 10.1089/end.2007.0109
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heminephrectomy in Horseshoe Kidney Using Bipolar Energy: Report of Three Cases

Abstract: Variability in blood supply, the renal isthmus, and abnormal kidney location are unique features that contribute to making a laparoscopic approach for heminephrectomy in a horseshoe kidney technically challenging. We report three cases of laparoscopic heminephrectomy for benign disease in horseshoe kidneys using bipolar energy for transection of the isthmus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…16 In another study of three patients with horseshoe kidney who had laparoscopic heminephrectomy, a nonfunctional kidney-one due to trauma and the others due to kidney stone and UPJ obstruction-was stated as the etiological factor. 15 In this study, six patients with horseshoe kidney had laparoscopic heminephrectomy because of non-functional kidney. Of these patients, three had kidneys with function loss due to UPJ obstruction and three due to kidney stone.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…16 In another study of three patients with horseshoe kidney who had laparoscopic heminephrectomy, a nonfunctional kidney-one due to trauma and the others due to kidney stone and UPJ obstruction-was stated as the etiological factor. 15 In this study, six patients with horseshoe kidney had laparoscopic heminephrectomy because of non-functional kidney. Of these patients, three had kidneys with function loss due to UPJ obstruction and three due to kidney stone.…”
Section: Discussionmentioning
confidence: 97%
“…14 While this helps significantly with laparoscopic heminephrectomy for malignity, due to the tendency for atrophic veins to exist in non-functional kidneys, some do not suggest its routine use. 15 Of the six cases included in this study, the first three did not use preoperative CT angiography, but because of aberrant renal arteries and veins apart from the main renal artery and renal vein, CT angiography was used in the last three cases (Figure 2). In order to avoid preoperative vein complications, we suggest preoperative CT angiography for all patients before they undergo heminephrectomy in response to malignity in a horseshoe kidney or non-functional kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported cases of non-functioning horseshoe kidney heminephrectomy with use of bipolar coagulation [24], microwave coagulation [25], harmonic scalpel [5], Ligasure ® [16], and an endostapler [24, 26] for the division of the isthmus. Coagulation seems to be insufficient, and in our opinion, stitches on the parenchyma are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In this series, one patient developed a urinoma. Additionally, authors from Iran reported on the successful use of bipolar energy to transect the isthmus of a horseshoe kidney in three patients undergoing laparoscopic heminephrectomy for benign disease [11]. Researchers from Long Island Jewish Medical Center found the laparoscopic endostapler to be a useful adjunct for division of the isthmus during laparoscopic heminephrectomy in the horseshoe kidney [12].…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%